A Grey Prediction Algorithm for Enterprise Human Resource Management Validity Model Construction and Improvement. (8th July 2022) - Yang, Yajing
Abstract : With the deepening development of economic globalization and world economic integration, all enterprises are faced with an increasingly complex and competitive living environment. Therefore, it is particularly important to formulate a human resource strategy suitable for the enterprise's own development to cope with the external challenges and external competition of the enterprise. However, in the current management practice of state-owned enterprises including power supply enterprises in our country, it is rare to make strategic decisions on human resources by applying scientific, effective, and complete mathematical models. Taking construction enterprises as an example, this study combines human resource management, enterprise management, project management, comprehensive evaluation, and grey system and other theories to systematically study the effect of human resource management in enterprises, and finally constructs a suitable evaluation method for construction enterprises, and an assessment model for diagnosing its human resource management status. We provide practical guidance for the management of human resources in construction enterprises, which is conducive to human resource workers to discover existing problems in time and make improvements, give full play to the potential of human resources, and improve the level of human resource management and the value of enterprises.